Log Files Can and Should be Prepared for a Functionalistic Approach - Bergenholtz, Henning; Johnsen, Mia (Lexikos, 2007)
Abstract: User surveys of printed dictionaries may be characterised as non-representative and non-realistic laboratory tests, often with retrospective questions based on memory. Log file analy-ses concerning the use of Internet dictionaries, on the other hand, are based on large numbers of users and look-ups. However, log file analyses have also been characterised by a juggling of num-bers based on data calculations of limited direct relevance to practical and theoretical lexicography. This article proposes the development of lexicographically relevant log files for the use in log file analyses in order to give a true picture of how and why different dictionaries are employed for different purposes.Keywords: LEXICOGRAPHY, LOG FILES, DICTIONARY, INTERNET DICTIONARY, SEARCH OPTIONS, DICTIONARY FUNCTION, RECEPTION, TEXT PRODUCTION, TRANS-LATION, COMMUNICATIVE FUNCTION, COGNITIVE FUNCTION, DICTIONARY USE, USER SURVEY, LEMMA, DICTIONARY ITEM, USER NEEDSOpsomming: Loglêers kan en behoort voorberei te word vir 'n funksiona-listiese benadering. Gebruikersopnames van gedrukte woordeboeke kan gekarakteriseer word as nieverteenwoordigende en nierealistiese laboratoriumtoetse, dikwels met retrospektiewe vrae gebaseer op geheue. Loglêerontledings betreffende die gebruik van Internetwoordeboeke, aan die ander kant, is gebaseer op groot getalle gebruikers en raadplegings. Loglêerontledings word egter ook gekenmerk deur 'n gegoël met getalle gebaseer op databerekeninge van beperkte direkte tersaaklikheid vir die praktiese en teoretiese leksikografie. Hierdie artikel stel die ontwikkeling van leksikografies tersaaklike loglêers voor vir gebruik in loglêerontledings om 'n ware beeld te gee van hoe en waarom verskillende woordeboeke vir veskillende doeleindes aangewend word.Sleutelwoorde: LEKSIKOGRAFIE, LOGLÊERS, WOORDEBOEK, INTERNETWOORDE-BOEK, SOEKKEUSES, WOORDEBOEKFUNKSIE, ONTVANGS, TEKSPRODUKSIE, VERTA-LING, KOMMUNIKATIEWE FUNKSIE, KOGNITIEWE FUNKSIE, WOORDEBOEKGEBRUIK, GEBRUIKERSOPNAME, LEMMA, WOORDEBOEKITEM, GEBRUIKERSBEHOEFTES